KARBON TERSIMPAN DI TATA GUNA LAHAN SUB-SUB DAS KHILAU DAS SEKAMPUNG - Ratih Rinda Ningsih; Irwan Sukri Banuwa; Duryat -; Slamet Budi Yuwono (Lambung Mangkurat University-Indonesia, 2021)
The khilau is one of sub-watershed of the sekampung watershed. The area was very important due to its function as catchment area which is also located close to TAHURA (great forest park ) Wan Abdurrachman, there for sub-watershed khilau plays a very strategic role in the preservation of biodiversity and climate change. The study aims were to analyze the carbon determine the total carbon dioxide uptake and oxygen release in the khilau sub-watershed. The carbon stored was extimated by using allometric equation the biomass tree. The biomass expantion factor was employed estimated of biomass. The carbon conten multiplication with the value of the conversion of carbon elements to carbon dioxide, while for the oxigen release was estimated by multiplying the value of carbon squestration by the conversion value of carbon atoms to oxygen based on atomic weight. The result showed that carbon stored in the forest was 141,69 tons/ha, it was greater than agroforetry (75,33 tons/ha), shrubs (24,74 tons/ha), annual plant (11,13 tons/ha) and paddy fields (3,45 tons/ha) with a total area of forest 52,22 ha, agroforestry 457,86 ha, shrub 28,74 ha, annual plant 84,8 ha and paddy fields 2,36 ha. The total carbon dioxide absorbtion was 159.832,73 tons and oxygen release was 426.220,61 tons.